DEVELOPING SCIENCE LEARNING INSTRUMENTS BASED ON LOCAL WISDOM TO IMPROVE STUDENT’S CRITICAL THINKING SKILLS (Department of Physics, Faculty of Mathematics and Natural Sciences, 2015)
This research aims to develop learning instruments of science i.e. textbook, student worksheet, syllabus, and lesson plan based on local wisdom that can improve critical thinking skills of junior high school students. Indicators of student's critical thinking skills include interpretation, analysis, evaluation and inference. This study is a Research and Development by using analysis, desaign, development, implementation and evaluation (ADDIE) method. Expert validation was conducted with the expert test related to the format, content/material, and language. The instruments ware used on the collection data are documentations, validation sheets, observation sheets, and tests. The result of the instrument in the 7th grade of junior high school at Bustanul Ulum Panti Jember showed that there are the improvement of critical thinking skills of student based on the data from test and observation. According to indicator of critical thinking skills, the n-gain value is around 0.47, means moderate interpretation. The conclusions of this research are the learning instruments of science based on local wisdom which develope in the valid category is quite effective to improve students' critical thinking skills.Penelitian ini bertujuan mengembangkan perangkat pembelajaran IPA yang berupa Buku ajar, LKS, Silabus, dan RPP berbasis kearifan lokal untuk meningkatkan kemampuan berpikir kritis siswa SMP. Indikator kemampuan berpikir kritis siswa mencakup interprestasi, analisis, evaluasi dan inferensi. Penelitian ini merupakan penelitian Research and Development dengan metode Analysis, Desaign, Development, Implimentation and Evaluastion (ADDIE). Validasi ahli dilakukan dengan uji expert terkait dengan format, isi/materi, dan bahasa. Instrumen yang digunakan dalam pengambilan data adalah dokumentasi, lembar validasi, lembar observasi, dan tes. Hasil ujicoba instrumen di kelas VII SMP Bustanul ulum Panti Kabupaten Jember menunjukkan adanya peningkatan kemampuan berpikir kritis siswa, baik yang diambil dari teknik tes maupun observasi. Berdasarkan indikator kemampuan berpikir kritis diperoleh nilai rata-rata N gain 0,47 dengan interpretasi sedang. Simpulan penelitian ini menunjukkan perangkat pembelajaran IPA berbasis kearifan lokal yang dikembangkan dalam katagori valid sehingga cukup efektif dalam meningkatkan kemampuan berpikir kritis siswa.